Missional Congregations as Public Companions with God in Global Civil Society: Vocational Imagination and Spiritual Presence. Issue 2 (June 2015) - Simpson, Gary M.
Abstract This article explores the intersection of missional ecclesiology and civil society studies and proposes that the Holy Spirit is calling emerging missional congregations to the vocation of public companions with God in global civil society. This congregational vocation of public companion entails four dimensions of missional congregations' spiritual presence within civil society: perichoretic communion, prophetic speech, sapiential wisdom, and pacific action.